Substituted 2,2′-Bipyridines by Nickel Catalysis: 4,4′-Di-tert-butyl-2,2′-bipyridine - Buonomo, Joseph A.; Everson, Daniel A.; Weix, Daniel J. (Synthesis, 2013)
A simple, ligand-free synthesis of the important bipyridyl ligand 4,4′-di-tert-butyl-2,2′-bipyridine is presented. 5,5′-Bis(trifluoromethyl)-2,2′-bipyridine is also synthesized by the same protocol. The syntheses efficiently couple the parent 2-chloropyridines by a nickel-catalyzed dimerization with manganese powder as the terminal reductant.
Keywords: nickel; 4,4′-di-tert-butyl-2,2′-bipyridine; pyridine; catalysis; reductive